Associations of Cumulative Adulthood, Childhood and Lifelong Insulin With Adulthood Retinal Microvasculature - Repo, Oskari; Juonala, Markus; Rovio, Suvi P.; Mykkänen, Juha; Nevalainen, Jaakko; Kähönen, Mika; Lehtimäki, Terho; Laitinen, Tomi P.; Viikari, Jorma; Raitakari, Olli; Tapp, Robyn; Pahkala, Katja (ENDOCRINE SOC, 2025)
Context
Exogenous insulin is reported to have both vasodilatory and vasoconstrictive effects on microvasculature. Little is known about the associations of long-term endogenous insulin exposure with microvasculature.
Objective
To test the hypothesis that long-term exposure to high insulin levels in childhood and adulthood is associated with adverse changes in retinal microvasculature in adulthood in a population without diabetes.
Methods
We analyzed data derived from the longitudinal Cardiovascular Risk in Young Finns Study. The first cross-sectional study was conducted in 1980, and participants were followed for 31 years from childhood to adulthood with frequent follow-up visits. Fundus photos were taken in 2011, and microvascular outcome measures were derived in participants at the age of 34 to 49 years (n = 1684). After exclusion of individuals with diabetes or missing insulin measures, 1166 participants formed the population of the present study. Cumulative exposure as the area under the curve (AUC) for adulthood (10-year exposure between 2001 and 2011) and childhood (exposure between ages 6-18 years) insulin and other cardiovascular risk factors were determined. Additionally, adulthood and childhood cumulative AUCs were summarized to construct lifelong AUCs.
Results
Higher adulthood, childhood, and lifelong exposure for cumulative insulin was associated with decreased retinal arteriolar diameter when adjusted for age and sex and further for cumulative conventional cardiovascular risk factors.
Conclusion
Cumulative childhood, adulthood, and lifelong insulin are associated with decreased retinal arteriolar diameter in adulthood in a population of participants without diabetes, independently of conventional cardiovascular risk factors.